2018
DOI: 10.21037/jovs.2017.11.08
|View full text |Cite
|
Sign up to set email alerts
|

Minimal-invasive thoracic surgery in pediatric patients

Abstract: During the last two decades, there was a tremendous development of video-assisted thoracoscopic surgery (VATS), especially in the field of video-assisted lung resections. This article describes the actually state of this surgical technique in the treatment of pediatric patients. The problems in practical application are illustrated as well as clinical results, like they are presented in literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Adult studies have shown that VATS is associated with a well described learning curve ( 84 ). The existence of a similar learning curve is seen in paediatric patients ( 78 , 85 ). As the number of cases are fewer in case of children so gathering experience takes longer and so is the training.…”
Section: Patient Selection Technical Issues and Tipssupporting
confidence: 54%
See 1 more Smart Citation
“…Adult studies have shown that VATS is associated with a well described learning curve ( 84 ). The existence of a similar learning curve is seen in paediatric patients ( 78 , 85 ). As the number of cases are fewer in case of children so gathering experience takes longer and so is the training.…”
Section: Patient Selection Technical Issues and Tipssupporting
confidence: 54%
“…However, in infants and smaller children paediatric VATS demands very small calibre instruments which may not be easily available. Due to lower incidence of cases and technical and structural problems there is a slower progress in achieving experience in VATS even among purely paediatric centres ( 78 ). This leads to scarcity of adequate training facilities when compared with adults.…”
Section: Patient Selection Technical Issues and Tipsmentioning
confidence: 99%